Swedish National Multicenter Study on Head and Neck Cancer of Unknown Primary: Prognostic Factors and Impact of Treatment on Survival - Axelsson, Lars; Holmberg, Erik; Nyman, Jan; Högmo, Anders; Sjödin, Helena; Gebre-Medhin, Maria; von Beckerath, Mathias; Ekberg, Tomas; Farnebo, Lisa; Talani, Charbel; Spak, Lena Norberg; Notstam, Isak; Hammerlid, Eva (International Archives of Otorhinolaryngology, 2020)
Introduction Head and neck cancer of unknown primary (HNCUP) is a rare condition whose prognostic factors that are significant for survival vary between studies. No randomized treatment study has been performed thus far, and the optimal treatment is not established.Objective The present study aimed to explore various prognostic factors and compare the two main treatments for HNCUP: neck dissection and (chemo) radiation vs primary (chemo) radiation.Methods A national multicenter study was performed with data from the Swedish Head and Neck Cancer Register (SweHNCR) and from the patients' medical records from 2008 to 2012.Results Two-hundred and sixty HNCUP patients were included. The tumors were HPV-positive in 80%. The overall 5-year survival rate of patients treated with curative intent was 71%. Age (p < 0.001), performance status (p= 0.036), and N stage (p= 0.046) were significant factors for overall survival according to the multivariable analysis. Treatment with neck dissection and (chemo) radiation (122 patients) gave an overall 5-year survival of 73%, and treatment with primary (chemo) radiation (87 patients) gave an overall 5-year survival of 71%, with no significant difference in overall or disease-free survival between the 2 groups.Conclusions Age, performance status, and N stage were significant prognostic factors. Treatment with neck dissection and (chemo) radiation and primary (chemo) radiation gave similar survival outcomes. A randomized treatment study that includes quality of life is needed to establish the optimal treatment.
Keywords: head and neck cancer; cancer of unknown primary; prognostic factors; human papillomavirus; treatment